2020
DOI: 10.1108/jfep-02-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management, policy uncertainty and firm life cycle stages: evidence from publicly traded companies in the USA and Brazil

Abstract: Purpose This paper aims to investigate the combined effect of economic policy uncertainty (EPU) and the firm life cycle on the degree of accrual-based earnings management of publicly traded companies in the USA and Brazilian stock markets. Design/methodology/approach The EPU index used was the one developed by Baker et al. (2016), the Kothari et al. (2005) model was used in the main analysis to obtain the discretionary accruals and the classification of firms into different life cycles was based on the Dicki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
1
19
1
2
Order By: Relevance
“…The max value is 1.291 compared to À0.0000837 (Phuong & Hung, 2020). In term of AEM, the DAs variables (aem_jones and aem_kothari) has mean value of 0.000 and À0.001, respectively, that lower than research of Roma et al (2020) with US firm. Besides, the mean value of firm size by assets after logarithm (size) is 26.948 higher than in the study of Phuong and Hung (2020).…”
Section: Descriptive Statisticsmentioning
confidence: 92%
See 1 more Smart Citation
“…The max value is 1.291 compared to À0.0000837 (Phuong & Hung, 2020). In term of AEM, the DAs variables (aem_jones and aem_kothari) has mean value of 0.000 and À0.001, respectively, that lower than research of Roma et al (2020) with US firm. Besides, the mean value of firm size by assets after logarithm (size) is 26.948 higher than in the study of Phuong and Hung (2020).…”
Section: Descriptive Statisticsmentioning
confidence: 92%
“…Kale and Almeida (2019) also proved that businesses in the recession have the poorest accrual quality and that life cycle stages affect accounting decisions. Besides, a vital relationship between OLC and DAs was found, and the degree of EM behaviors is different based on each circumstance (Roma et al, 2020). In the Chinese context, Hussain et al (2020) was found a positive relationship between AEM and the decline stage.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Temuan ini menunjukan bahwa dalam menilai kinerja serta prospek masa depan perusahaan yang berada pada tahap decline, investor lebih menekankan pada aliran kas dari aktivitas operasi. Dalam hal ini aliran kas operasi mengandung informasi tentang kemapuan perusahaan mampu menghasilkan modal atas kegiatan operasinya sendiri, yakni membayar kepada para debitur dalam kasus likuidasi (Roma et al, 2020).…”
Section: Tabel 2 Hasil Uji Regresiunclassified
“…This uncertainty dimension concerns the unpredictability of the economic policy by government agents, related to who will make the decisions when taken over; and what their future effects on the economy are (Baker et al, 2016). Such uncertainty can change the dynamics of firms' financial decisions, which can delay their investments (Akron et al, 2020;Gulen & Ion, 2015), increase their cash holdings for speculation and precaution (Duong et al, 2020), reduce debt levels (Li & Qiu, 2021), pay more dividends as a form of signaling (Attig et al, 2021) and even reduce earnings management practices depending on their stage in the life cycle (Roma et al, 2020). Specifically, in the case of M&A, empirical evidence for the US suggests that a shock of economic policy uncertainty may negatively affect the volume and value of acquisitions (Bonaime et al, 2018).…”
Section: Introductionmentioning
confidence: 99%